Microbleed Status and 3-Month Outcome After Intravenous Thrombolysis in 717 Patients With Acute Ischemic Stroke. Issue 9 (September 2015) - Turc, Guillaume; Sallem, Asmaa; Moulin, Solène; Tisserand, Marie; Machet, Alexandre; Edjlali, Myriam; Baron, Jean-Claude; Leclerc, Xavier; Leys, Didier; Mas, Jean-Louis; Cordonnier, Charlotte; Oppenheim, Catherine
<x xml:space="preserve">Abstract</x> Background and Purpose— Whether cerebral microbleeds (CMBs) detected on pretreatment magnetic resonance imaging increase the risks of symptomatic intracranial hemorrhage (sICH) and, most importantly, poor outcome in patients treated by intravenous thrombolysis for acute ischemic stroke is still debated. We assessed the effect of CMB presence and burden on 3-month modified Rankin Scale and sICH in a multicentric cohort. Methods— We analyzed prospectively collected data of consecutive patients solely treated by intravenous thrombolysis for acute ischemic stroke, in 2 centers where magnetic resonance imaging is the first-line pretreatment imaging. Neuroradiologists blinded to clinical data rated CMBs on T2* sequence using a validated scale. Logistic regressions were used to assess relationships between CMBs and 3-month modified Rankin Scale or sICH. Results— Among 717 patients, 150 (20.9%) had ≥1 CMBs. CMB burden was associated with worse modified Rankin Scale in univariable shift analysis (odds ratio, 1.07; 95% confidence interval, 1.00–1.15 per 1-CMB increase; P=0.049), but significance was lost after adjustment for age, hypertension, and atrial fibrillation (odds ratio, 1.03; 95% confidence interval, 0.96–1.11 per 1-CMB increase; P=0.37). Results remained nonsignificant when taking into account CMB location or presumed underlying vasculopathy. The incidence of sICH ranged from 3.8% to 9.1%, depending on the definition. Neither CMB presence, burden, location, nor presumed underlying vasculopathy was independently associated with sICH. Conclusions— Poor outcome or sICH was not associated with CMB presence or burden on pre–intravenous thrombolysis magnetic resonance imaging after adjustment for confounding factors. An individual patient data meta-analysis is needed to determine whether a subgroup of patients with CMBs carries an independent risk of poor outcome that might outweigh the expected benefit of intravenous thrombolysis.